Are they finely tuned?: Mapping the CEFR level of the reading texts of the English textbook for grade 10 of Indonesian senior high school - Dairabi Kamil (Universitas Sulawesi Barat, 2023)
This study sought to investigate the CEFR level of the reading passages of the English textbook for Grade 10 of Indonesian senior high school written within the framework of the newly launched Kurikulum Merdeka and the extent to which the levels match the intention of the curriculum. Drawing on a quantitative approach, the data for the study were 16 reading passages of the textbook and analyzed using an online program for analyzing the CEFR level of texts. The results showed that only 2 out of the 16 passages were of B1 CEFR level, the level the textbook is intended to be by the curriculum. The rest range from B2 to C2 CEFR level indicating that, in general, the passages are higher in their CEFR levels than that stipulated by the curriculum